Multiparametric magnetic resonance imaging for the differential diagnosis between granulomatous prostatitis and prostate cancer: a literature review to an intriguing diagnostic challenge - Gaudiano, Caterina; Renzetti, Benedetta; De Fino, Cristina; Corcioni, Beniamino; Ciccarese, Federica; Bianchi, Lorenzo; Schiavina, Riccardo; Droghetti, Matteo; Giunchi, Francesca; Brunocilla, Eugenio; Fiorentino, Michelangelo (Frontiers in Oncology, 2023)
Multiparametric magnetic resonance imaging (mpMRI) is currently the most effective diagnostic tool for detecting prostate cancer (PCa) and evaluating adenocarcinoma-mimicking lesions of the prostate gland, among which granulomatous prostatitis (GP) represents the most interesting diagnostic challenge. Granulomatous prostatitis consists of a heterogeneous group of chronic inflammatory lesions which can be differentiated into four types: idiopathic, infective, iatrogenic and associated with systemic granulomatous disease. The incidence of GP is growing due to the increase of endourological surgical interventions and the adoption of intravesical instillation of Bacillus Calmette-Guerin-induced in patient with non-muscle invasive bladder cancer, therefore the hardship is to identify specific features of GP on mpMRI to avoid as much as possible the use of transrectal prostate biopsy.